Ten yr of pediatric heart transplantation: A report from the Pediatric Heart Transplant Study. (26th February 2013) - Dipchand, Anne I.; Kirk, Richard; Mahle, William T.; Tresler, Margaret A.; Naftel, David C.; Pahl, Elfriede; Miyamoto, Shelley D.; Blume, Elizabeth; Guleserian, Kristine J.; White‐Williams, Connie; Kirklin, James K.
Abstract: The PHTS was founded in 1991 as a not‐for‐profit organization dedicated to the advancement of the science and treatment of children during listing for and following heart transplantation. Now, 21 yr later, the PHTS has contributed significantly to the field, most notably in the form of outcomes analyses and risk factor assessment, in addition to amassing the most detailed dataset on pediatric heart transplant recipients worldwide. The purpose of this report is to review the last decade of pediatric patients listed for heart transplantation (January 1, 2000–December 31, 2009) and summarize the changes, trends, outcomes, and lessons learned.